2019
DOI: 10.4081/mrm.2019.5
|View full text |Cite
|
Sign up to set email alerts
|

Indoor bacterial load and its correlation to physical indoor air quality parameters in public primary schools

Abstract: Background: Poor indoor air quality is a great problem in schools due to a high number of students per classroom, insufficient outside air supply, poor construction and maintenance of school buildings. Bacteria in the indoor air environment pose a serious health problem. Determination of bacterial load in the indoor environment is necessary to estimate the health hazard and to create standards for indoor air quality control. This is especially important in such densely populated facilities like schools. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…Poor indoor air quality, which is a serious problem in schools due to the large number of students in the classroom, and insufficient internal air exchange, were reported by Andualum et al [26]. Similar to our study, those authors noted a clear increase in bacterial numbers after classes, and that temperature, relative humidity, and dust concentrations were associated with bacterial contamination.…”
Section: Discussionsupporting
confidence: 90%
“…Poor indoor air quality, which is a serious problem in schools due to the large number of students in the classroom, and insufficient internal air exchange, were reported by Andualum et al [26]. Similar to our study, those authors noted a clear increase in bacterial numbers after classes, and that temperature, relative humidity, and dust concentrations were associated with bacterial contamination.…”
Section: Discussionsupporting
confidence: 90%
“…Ninty‐five percent of the airborne particles were having a diameter of less than 1 µm, which showed a significant correlation with concentrations of culturable airborne bacteria [30]. A strong correlation was found between PM 2.5 and total airborne bacteria [13,86]; however, Bragoszewska et al [87] found their negative correlation. Some studies showed no significant correlation between fungal levels and particle counts [30], whereas Armadans‐Gil et al [88] observed a positive correlation between airborne fungi and particle sizes greater than 0.5 µm as well as greater than 1 µm in the hospital rooms.…”
Section: Environmental Factors: Indoor and Outdoormentioning
confidence: 99%
“…Again, Sule, et al [27] stated that ventilation, health status, human traffic and activities are some of the factors which could increase the level of microorganisms in the indoor air. The variation of bacterial load in indoor environments could also be due to environmental factors such as ventilation system of rooms, temperature, humidity, and particulate matter concentration [28].…”
Section: Discussionmentioning
confidence: 99%